2021
DOI: 10.18260/2-1-370.660-125552
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Principles of Biomaterials to Undergraduate Students During the COVID-19 Pandemic with At-Home Laboratory Experiments

Abstract: Cooper Union specializing in drug delivery, wound healing, and developing new polymeric biomaterials. At Cooper, she teaches courses in Materials Science, Biomaterials, and Drug Delivery. She earned her BS in Chemical Engineering from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Pre/post-tests demonstrated that students experienced significant learning gains of 33 percentage points from completing this IBL mechanobiology module. These learning gains were consistent with published bioengineering educational modules that found learning gains of about 50 percentage points for freshman engineering students [ 46 , 55 ], 15 percentage points for senior engineering students [ 10 ], and 15–30 percentage points for classes with mixed undergraduate students [ 12 , 13 ]. Since our cohort contained students from all undergraduate levels, we expected our learning gains to be within this range.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Pre/post-tests demonstrated that students experienced significant learning gains of 33 percentage points from completing this IBL mechanobiology module. These learning gains were consistent with published bioengineering educational modules that found learning gains of about 50 percentage points for freshman engineering students [ 46 , 55 ], 15 percentage points for senior engineering students [ 10 ], and 15–30 percentage points for classes with mixed undergraduate students [ 12 , 13 ]. Since our cohort contained students from all undergraduate levels, we expected our learning gains to be within this range.…”
Section: Discussionsupporting
confidence: 87%
“…In the first portion of the activity, students tested how the concentration of agar in pre-crosslinked polymer solutions would impact the compressive properties of resultant physically entangled hydrogels. To do this, we adapted a previously described method for students to conduct at-home compressive testing of gelatin hydrogels [ 12 ]. First, students calculated the volumes of agar and LB broth required to make 100 mL hydrogel cubes with 0.75–3% agar.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,33,41,43 To help address these gaps, the authors previously partnered with the Young Eisner Scholars, a program designed to empower middle and high school students from underserved communities, to adapt an undergraduate-level, at-home inquiry-based learning module for middle school outreach. 34,35 The authors hypothesize that this IBL bioadhesives module can be similarly adapted to an outreach activity for middle and high school students. For an in-person middle or high school student outreach activity, instructors should provide supervision when using the GTA crosslinker and use the experience as an opportunity to teach about chemical safety.…”
Section: Diversity Equity and Inclusionmentioning
confidence: 99%
“…The Covid-19 pandemic restricted students' access to laboratories and research facilities, and most field trips and excursions had been cancelled. HEI providers sought alternative strategies to prepare students for a successful post-graduation career, including access to interactive online lab sessions, the introduction of lab or field virtual simulations, and lab/field activities to be conducted at home with any required material sent by post to all participating students [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%